2021
DOI: 10.3390/w13243493
|View full text |Cite
|
Sign up to set email alerts
|

Ion Flotation of Ytterbium Water-Salt Systems—An Innovative Aspect of the Modern Industry

Abstract: Considering the ever-increasing role of rare-earth elements (REE) in the modern hi-tech field, their effective use has tremendous significance, although the production process is inevitably linked to the large volumes of industrial ammonia effluents and heavy metal wastes. In the process of metallurgical separation of metals, the emission of large volumes of noxious gases and radioactive substances is inevitable. Lean technogenic raw material processing is sensible under the condition of the development of non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the majority of ion flotation studies used sodium dodecyl sulfate (NaDDS) as the surfactant (Table 4). Previous studies have shown that this technique could recover low-concentration REEs (10 -6 to 10 -3 M) with efficiencies of 57-98% [133][134][135][136][137][138][139][140]. Aside from NaDDS, other surfactants like monorhamnolipid [131,140], AKYPO RO 90 VG [141], and cetylpyridinium chloride (CPC) [142] have also been used.…”
Section: Ion Flotationmentioning
confidence: 99%
“…However, the majority of ion flotation studies used sodium dodecyl sulfate (NaDDS) as the surfactant (Table 4). Previous studies have shown that this technique could recover low-concentration REEs (10 -6 to 10 -3 M) with efficiencies of 57-98% [133][134][135][136][137][138][139][140]. Aside from NaDDS, other surfactants like monorhamnolipid [131,140], AKYPO RO 90 VG [141], and cetylpyridinium chloride (CPC) [142] have also been used.…”
Section: Ion Flotationmentioning
confidence: 99%
“…Values of the distribution coefficients were obtained and it was found that the addition of chloride ions had a tendency toward a decrease in the distribution coefficients and a shift of the maximum recovery to the range of higher pH values. The distribution coefficients reach the maximum value at a chloride concentration of 0.01 M. The oxalate complexes with long-chain fatty amines (especially tetradecylamine) Sodium lauryl sulfate (SLS) Lusher andSeba, 1965 Abdeldaim et al, 2014 Ion flotation of cerium, samarium, and europium from nitrate solutions with sodium dodecyl sulfate, as flotation reagent, were reported (Chrikst et al, 2009;Lobacheva et al, 2013). The dependences of the distribution coefficients of rare earth ions in the ion flotation on pH of an equilibrium aqueous phase were obtained.…”
Section: Separation Of Rare and Alkaline Earth Metalsmentioning
confidence: 99%